Hierarchical Self-Assembly of Microgel-Modified Biomaterials Surfaces. Issue 1622 (2014) - Wu, Yong; Liang, Jing; Wang, Qichen; Libera, Matthew
ABSTRACT: Microgels are hydrogel particles with micron and sub-micron diameters. They have beendeveloped, studied, and exploited for a broad range of applications because of their uniquecombination of size, soft mechanical properties, and controllable network properties. We havebeen using microgels to modulate the properties of surfaces to differentially control theirinteractions with tissue cells and bacteria. The long-term goal is to create biomaterials thatpromote healing while simultaneously inhibiting infection. Because poly(ethylene glycol) [PEG]is used in a number of FDA-approved products and has well-known antifouling properties, wework primarily with PEG-based microgels. We render these anionic either by copolymerizationwith monomeric acids or by blending with polyacids. Both methods produce pH-dependentnegative charge. Surfaces, both planar 2-D surfaces as well as topographically complex 3-Dsurfaces, can be modified using a hierarchy of non-line-of-sight electrostatic depositionprocesses that create biomaterials surfaces whose cell adhesiveness is modulated by a submonolayerof microgels. Average inter-microgel spacings of 1-2 microns exploit naturaldifferences between staphylococcal bacteria and tissue cells, which open the opportunity todifferentially control surface interactions with them based on length-scale effects. Afterdeposition, the microgels can be loaded with a variety of small-molecule, cationic antimicrobials.The details of loading depend on the relative sizes of the antimicrobials and the microgelnetwork structure as well as on the amount and spatial distribution of electrostatic charge withinboth the microgel and on the antimicrobial. The exposed surface between microgels can befurther modified by the adsorption of adhesion-promoting proteins such as fibronectin viaelectrostatic interaction. This approach combines a rich interplay of microgel structure andchemistry as a key component in a simple and translatable approach to modulate the surfaceproperties of next-generation biomaterials.